2013
DOI: 10.1016/j.ijsu.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Surgical experts: Born or made?

Abstract: The concept of surgical expertise and the processes involved in its development are topical, and there is a constant drive to identify reliable measures of expert performance in surgery. This review explores the notion of whether surgical experts are "born" or "made", with reference to educational theory and pertinent literature. Peer-reviewed publications, books, and online resources on surgical education, expertise and training were reviewed. Important themes and aspects of expertise acquisition were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 48 publications
1
46
0
2
Order By: Relevance
“…Surgical training increasingly relies on trainees being comfortable with various techniques to achieve their full potential [26]. Events such as simulation training provide an opportunity for students to familiarise themselves with basic surgical procedures and techniques in a safe environment allowing graduating doctors to develop basic surgical competency.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical training increasingly relies on trainees being comfortable with various techniques to achieve their full potential [26]. Events such as simulation training provide an opportunity for students to familiarise themselves with basic surgical procedures and techniques in a safe environment allowing graduating doctors to develop basic surgical competency.…”
Section: Discussionmentioning
confidence: 99%
“…A long-standing debate exists over whether surgeons are ‘born’ or ‘made’, as discussed by Sadideen et al 18 This thorough evaluation of the literature suggests that surgical expertise is reached through practice, that is, surgeons are made, not born. It does, however, acknowledge the fact that the surgical expert should possess a strong set of ‘non-technical skills’, including depth of knowledge, communication skills and decision making, along with the acquisition of ‘technical’ psychomotor skills.…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors have explored the possibility of using this type of NTs to assess dexterity in surgeons [7]. Researchers have found that there is a significant relationship between scores on NTs that evaluate FMS and the performance of trainees in surgical procedures [65,66,67]. Moreover, Kyle et al [68] suggest that NTs may be used to identify those novice trainees with lower FMS scores, who might require additional support for their learning of some specific technical tasks.…”
Section: Methodsmentioning
confidence: 99%
“…Even if the “ideal” amount of movements is unknown, it is also possible to make comparisons with the amount of movements required by a very skilled individual. On surgical simulators, a parameter called movement economy is used; it is calculated as a ratio between the average of movements required by skilled surgeons (taken as a gold standard) and the average of movements performed by a trainee [65]. …”
Section: Methodsmentioning
confidence: 99%